OPTIMALISASI ISOLASI DAN PURIFIKASI DNA Petunia hybrida SERI ROSE PICOTEDENGAN KIT ISOLASI GENEAID - Naailatu Nur Azizah; Muthia Naila Mazieda; Dwi Listyorini; Dahlia Dahlia (Universitas Sebelas Maret, 2014)
Abstract - Petunia has been used as research object on flavonoids studies especially anthocyanin biosynthesis. Hf1 gene encode F3'5'H enzyme which plays a role in the synthesis of color in Petunia. Research on the regulation of Petunia color is potential for the development of ornamental plant breeding in Indonesia, hence the information regarding the gene analysis is necessary. Recently, there are many reagent kits for the isolation and purification of plant DNA available, each has different protocols regarding the special character of plant tissue with various secondary metabolites accumulation. Secondary metabolites in plants have different chemical contents, for that reason its needs to develop a proper protocol resulting in pure DNA with high concentrations. This study aims to obtain the effective and efficient DNA isolation and purification protocol for Petunia hybrida. Optimization results showed that samples immersed in absolute ethanol for two days then dried and stored in the freezer until used have given the optimal results for further analysis. The total DNA concentration was 129.3 ng / µl with purity of 1,87. Keywords: Isolation and purification technique DNA, Petunia hybrida, Isolation Kit Geneaid